MODEM PLC AS ONE COMPONENT OF THE INTERNET CONNECTION VIA POWER CABLE - Mohamad Fauzi; Luyung Dinaini, SKom, MM (Jurnal Sistem Komputer, 2003)
Communication via the power cord (Power Line Communication), is something the local loop network technology, known as a technology "Las Mile", which utilizes telecommunications network Infrastructure. In Indonesia it is still common. however, the parties involved in this case the PLN (State Electricity Company) has been disseminating the use of electrical cable as a medium of computer networks, eg for accessing the Internet and collaborate antarkomputer very quickly. PLC technology has many advantages, diataranya terms of the cost of using the Internet with modern furniture is very cheap because the PLC is used that is fixed tariff rate, where in so we can pay to use the internet service this month both internet usage and long distance telephone, modem berbedadengan ordinary all use electricity and telephone tariffs, so that both of them became swollen fees (expensive), another advantage is speed of data transfer where the data access rate of about 3.2 up to 5.6 megabits per second. This is the same value as in the use of cellular networks for personal and internet access was very adequate. meaning for the transfers amounted to 50 Megabytes of data, only takes about one minute, another advantage that is flexible, and access without cable, so that using reknologi PLC can be made as a means to accelerate the improvement of the quality of human resources and their economic growth in Indonesia in general.